'Islamic humanism': another form of universalism in contemporary Sufism. Issue 2 (3rd April 2023) - Piraino, Francesco
ABSTRACT: Contemporary Sufi orders in Western societies have been often described as 'universal', implying a conceptualisation of religion that transcends religious and cultural boundaries. This article challenges a univocal understanding of universalism, arguing for a plurality of universalist discourses, which entail different relations with otherness, practices, organisational structures, and politics. This article shows the continuities and discontinuities among different competing universalist discourses present in contemporary Sufism and Islam, such as Guénonian-Traditionalism, the New Age, and neo-liberalism. Furthermore, it describes another universalist discourse which has not been previously discussed in relation to contemporary Sufism, defined as 'Islamic humanism', which focuses on (1) the anthropo-cosmic role of the human being, connecting God, nature, and humankind; (2) a universal truth, which goes beyond religious and cultural differences, but is inscribed in Islam; (3) a pluralistic epistemology merging Islamic, natural, and social sciences; and (4) a sense of responsibility towards society, which implies a socio-political engagement.